Foliar spraying of Mn with addition of Si increases phenolic compound, photosynthetic efficiency, productivity and the protein content of the soybean crop - Rocha, Ian Lucas de Oliveira [UNESP]; de Mello Prado, Renato [UNESP]; Oliveira, Kamilla Silva [UNESP]; da Silva, Dalila Lopes; Abreu-Junior, Cassio Hamilton (Springer Nature, 2022)
The present study evaluated whether manganese (Mn) combined with silicon (Si) added to the foliar spray solution favors the physiological aspects, productivity, and protein content of grains in Mn-deficient soybean crops. The experiment was carried out to test four concentrations of Mn (0.00, 0.29, 0.58, and 0.87 g L−1) as chelate with added Si (0.48 g L−1) as potassium silicate and without Si (control), following a 4 × 2 factorial scheme, arranged as randomized block design with five replications. The treatments were applied via foliar in the V6, V8, R1, and R2 phenological stages of the soybean crop. Soybean plants in the control group demonstrated deficiency symptoms such as physiological damage. The beneficials effects of Si on soybean crops it was due by reduction of oxidative stress, due to the increase in the content of the compound antioxidant phenol (9%), causing a decrease in the rate of cell leakage. This mechanism increased the relative chlorophyll index (6%) and the Fv/Fm, thus increasing leaf area, shoot dry mass, productivity (7%), and protein content (7%) in optimal concentration of Mn. The foliar spraying of optimal concentrations of Mn associated with Si is a promising way to improve the efficiency of soybean crops and to meet the nutritional demand for Mn.
Keywords: Abiotic stress; Beneficial element; Glycine max; Nutritional stress; Plant nutrition